ANALISIS PENGARUH KETIDAKPUASAN KONSUMEN, IKLAN, DAN KARAKTERISTIK KATEGORI PRODUK TERHADAP KEPUTUSAN PERPINDAHAN MEREK PADA SABUN PEMBERSIH WAJAH - Pramuninggar, Septiani; Bidayati, Utik (Universitas Ahmad Dahlan, 2012)
This study backs in the background by the emergence of the phenomenon of the emergence of new brands specifically for facial cleansing product category. A variety of brands of soap facial cleanser began competing, it is characterized by high levels of displacement brand of soap facial cleanser. The purpose of this study was to determine the effect of consumer dissatisfaction, advertising and the characteristics of the product categories of decisions of brand switching. The research was conducted on student Ahmad Dahlan School of Economics University of soap facial cleanser and the specified number of sample of 100 respondents by using multiple linear regression, t test, F test, and R2 (coefficient of determination).